Overconfidence in a career-concerns setting - Leonidas Enrique De La Rosa (Center for Economic Studies and ifo Institute (CESifo), 2008)
We study the effects of overconfidence in a two-period investment-decision agency setting. Under common priors, agent risk aversion implies inefficiently low first-period investment. In our model, principal and agent disagree about the profitability of the investment decision conditional on a given public signal. An overconfident agent believes that the principal will update her beliefs upwards more often than not. As a consequence, the agent overestimates the benefits of learning from first-period investment. This implies that agent overconfidence mitigates the agency problems arising from the agent's career concerns, even though an overconfident agent bears more project and reputational risk in equilibrium.
Keywords: D83; D84; D86; 330; Overconfidence; heterogenous beliefs; career concerns; Agency Theory; Investition; Karriereplanung; Erwartungstheorie; Lernprozess; Theorie